Proactive legal planning to avoid family business disputes - Bayan Saad Al-Shawaf; Rima Abdulrahman Al-Rashed; Rima Manea Al-Qahtani; Sarah Abdullah Al-Dakhil; Sham Mohammed Al-Qarni (International Journal of Law Research and Studies, 2025)
This research addresses the topic of proactive legal planning to avoid family business disputes. Its objectives can be summarized in achieving a set of scientific and practical goals that contribute to the study, discussion, and analysis of proactive legal plans to avoid family business disputes. These objectives are clarifying the concept and importance of family businesses, identifying the methods used in proactive legal planning to avoid family business disputes, clarifying the role of legislation in addressing family business disputes, and identifying the role of legislation in the sustainability and development of family businesses. The problem of this research revolved around the lack of proactive legal plans within family businesses to avoid any potential disputes, which can lead to conflicts that impact the stability and continuity of these businesses. Establishing clear legal frameworks to regulate relationships between family members, whether in management, the distribution of responsibilities, or decision-making, is often neglected from the outset. Such plans would effectively resolve these disputes before they occur. From this perspective, the research problem was shaped by the following main question: What are the proactive legal plans to avoid disputes within family businesses? This research reached several conclusions and recommendations, perhaps the most important of which is that the usage of proactive legal planning avoids family business disputes therefore raising the stability and longevity of family businesses. As a sound legal plan covers all areas of family business, such as governance, succession, and alternate resolutions that either resolve or prevent disputes. To further bolster this outcome, this paper also recommends the usage of specialized lawyers during the creation of a family charter to ensure the governance of the family business. This is in addition to securing alternative ways to solve or circumvent disputes within the family charter itself. The final recommendation is to place effective strategies that aim to manage the process of succession.